P150 Identification of features associated with poor outcomes in pediatric patients with ulcerative proctitis: A Multicentre Study From the Paediatric IBD Porto Group of ESPGHAN. (30th January 2023) - Tal-Shifman, N; Tzivinikos, C; Gasparetto, M; Serban, D E; Zifman, E; Hojsak, I; Ledder, O; Yerushalmy Feler, A; Rolandsdotter, H; Aloi, M; Bramuzzo, M; Buderus, S; et al.
Abstract: Background: Ulcerative proctitis (UP) is an uncommon presentation in paediatric patients with ulcerative colitis, accounting for <10% of cases. Here we aimed to characterize the clinical features and natural history of paediatric patients with UP, and to identify predictors of poor outcomes. Methods: A retrospective cohort study involving 37 sites affiliated with the IBD Interest group of ESPGHAN. Data were collected at different timepoints from patients diagnosed with UP aged <18 years between 01/01/2016-31/12/2020. Outcomes included time to initiation of systemic steroids, thiopurines or biologics, time to acute severe colitis (ASC), IBD-related admission and colectomy. Univariate cox regression was used to study the association between potential predictors and study outcomes. Results: Two hundred and fifty patients with UP were included, with a median age at diagnosis of 14.5 (IQR 12.3-15.9) years, and a median follow-up of 2.7 (IQR 1.7-3.9) years. The most common presenting symptoms were bloody stools (94%), abdominal pain (59%) and diarrhea (53%). At diagnosis, the median pediatric ulcerative colitis activity index (PUCAI) score was 25 (IQR 20-35), and only 3 patients (1.3%) presented with ASC. Most children had normal inflammatory markers and albumin levels. the median fecal calprotectin level was 720 mcg/g (IQR 310-1800), while 16 patients (9.9%) had a calprotectin level <100mcg/g at diagnosis. Administration of oral or topical 5-ASA resulted in clinical remission rates of 52% and 48%, respectively, by the end of induction, while the combination of both led to remission in 73% of patients. The rates of treatment escalation to thiopurines and biologics at 1, 3 and 5 years were 11%, 27% and 45%, and 11%, 23% and 45%, respectively (Figure 1). Within 5 years from diagnosis, 20% of patients had presented with ASC. The PUCAI score at diagnosis of UP was highly associated with initiation of systemic steroids, thiopurines or biologics, as well as later ASC event and IBD admission, while a Mayo endoscopic score of 3 was associated with the initiation of biologics and subsequent ASC event and IBD admission (Table 1). Seven patients (4%) underwent colectomy by the end of follow-up. Among the 151/250 patients who had a repeat endoscopy, only 16% achieved mucosal healing and in 48% inflammation extended proximally. Cecal patch (P=0.009) and higher PUCAI score (P=0.009) at diagnosis, as well as higher PUCAI score (P=0.009) and lack of steroid-free clinical remission (P=0.005) by the end of induction were associated with proximal disease extension. Conclusion: Disease burden is significant in paediatric patients that present with UP, with high rates of proximal disease extension and requirement for treatment escalation.